PENGARUH RETURN ON EQUITY, RETURN ON ASSET DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DI BURSA EFEK INDONESIA - Sofiah Br Sinaga; Argo Putra Prima (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2021)
The life of the Covid-19 Pandemic is a precious lesson for the network to spend money on fending off an unsure financial disaster withinside the future. One such funding is the sale and buy of stocks withinside the capital market. The motive of this take a look at is to peer the Return On Equity (ROE), Return On Assets (ROA) and enterprise length partly and concurrently to the enterprise price of the patron items enterprise sector. The studies approach of secondary statistics evaluation of the monetary statements of businesses indexed at the IDX from 2015-2019 the populace may be 60 populations and 34 samples of non-chance purposive sampling in order that one hundred seventy obtained. desk 1.97756 and chance (Sig.) of 0.756> 0.05 in order that H1 is rejected, ROA has no impact on organization price with a importance price of t remember 0.476> 0.05 and a chance price of 0.941 t desk 1.98447 in order that H3 is accepted. Simultaneously a substantial impact on organization price with an F calculated price of 21.067> 2, 66 from F desk and a importance price of 0.000